2016
DOI: 10.1111/jphp.12589
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid confers protection against gentamicin-induced oxidative damage, mitochondrial dysfunction and apoptosis-related nephrotoxicity

Abstract: Our findings suggest that EA treatment attenuates GEN-induced nephrotoxicity, which may be ascribed to its antioxidant and anti-apoptotic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 52 publications
9
42
0
Order By: Relevance
“…A study found that ellagic acid and punicalagin directly reduce ROS level produced by mitochondria . Ellagic acid was shown to exert an antioxidative effect via ameliorating mitochondrial dysfunction in concanavalin‐induced liver damage, gentamicin‐induced oxidative stress, and arsenic‐trioxide‐induced cytotoxicity in the human neuroblastoma cell line SH‐SY5Y . Cao et al .…”
Section: Mechanism Analysis Of Lipid Metabolism Regulated By Pomegranatementioning
confidence: 99%
“…A study found that ellagic acid and punicalagin directly reduce ROS level produced by mitochondria . Ellagic acid was shown to exert an antioxidative effect via ameliorating mitochondrial dysfunction in concanavalin‐induced liver damage, gentamicin‐induced oxidative stress, and arsenic‐trioxide‐induced cytotoxicity in the human neuroblastoma cell line SH‐SY5Y . Cao et al .…”
Section: Mechanism Analysis Of Lipid Metabolism Regulated By Pomegranatementioning
confidence: 99%
“…Therefore, apoptosis is considered as a potent therapeutic target for cancer treatment. It is believed that apoptosis can be triggered by diverse pro-apoptosis stimuli converging on mitochondria, which induces mitochondrial dysfunction such as mitochondrial depolarization, cytochrome c release, and caspase enzyme activation (8,9). In addition, mitochondria are the primary source of endogenous reactive oxygen species (ROS) and the targets of ROS in turn (9).…”
Section: Introductionmentioning
confidence: 99%
“…The staining extent was graded from 0 to 4 based on the percentage of immunoreactive tumor cells (0, 1-5, 6-25, 26-75 and 76-100%). A score ranging from 0 to 8 was calculated by multiplying the staining extent score with the staining intensity score, resulting in a low (0-4) level or a high (6)(7)(8) level for each sample (20).…”
Section: Introductionmentioning
confidence: 99%
“…Ellagic acid has been shown to specifically induce apoptosis in cancer cells [13, 14, 18, 3034] while having cytoprotective activity in non-transformed cells [2, 4, 10, 12, 19, 35]. To determine whether EA activated apoptotic pathways, we measured caspase-3 catalytic activities in cells treated with EA for 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…In non-transformed cells, EA is protective against oxidative insults [1012]. In contrast, EA has anti-proliferative and apoptotic effects in cancer cells.…”
Section: Introductionmentioning
confidence: 99%